MetMaxStruct: A Tversky-Similarity-Based Strategy for Analysing the (Sub)Structural Similarities of Drugs and Endogenous Metabolites - O'Hagan, Steve; Kell, Douglas B. (Frontiers in Pharmacology, 2016)
Background. Previous studies compared the molecular similarity of marketed drugs and endogenous human metabolites (endogenites), using a series of fingerprint-type encodings, variously ranked and clustered using the Tanimoto (Jaccard) similarity coefficient (TS). Because this gives equal weight to all parts of the encoding (thence to different substructures in the molecule) it may not be optimal, since in many cases not all parts of the molecule will bind to their macromolecular targets. Unsupervised methods cannot alone uncover this. We here explore the kinds of differences that may be observed when the TS is replaced – in a manner more equivalent to semi-supervised learning – by variants of the asymmetric Tversky (TV) similarity, that includes  and  parameters. Results. Dramatic differences are observed in (i) the drug-endogenite similarity heatmaps, (ii) the cumulative ‘greatest similarity’ curves, and (iii) the fraction of drugs with a Tversky similarity to a metabolite exceeding a given value when the Tversky  and  parameters are varied from their Tanimoto values. The same is true when the sum of the  and  parameters is varied. A clear trend towards increased endogenite-likeness of marketed drugs is observed when  or adopt values nearer the extremes of their range, and when their sum is smaller. The kinds of molecules exhibiting the greatest similarity to two interrogating drug molecules (chlorpromazine and clozapine) also vary in both nature and the values of their similarity as  and  are varied. The same is true for the converse, when drugs are interrogated with an endogenite. The fraction of drugs with a Tversky similarity to a molecule in a library exceeding a given value depends on the contents of that library, and  and  may be ‘tuned’ accordingly, in a semi-supervised manner. At some values of  and  drug discovery library candidates or natural products can “look” much more like (i.e. have a numerical similarity much closer to) drugs than do even endogenites. Conclusions. Overall, the Tversky similarity metrics provide a more useful range of examples of molecular similarity than does the simpler Tanimoto similarity, and help to draw attention